2021
DOI: 10.3390/biomedicines9101301
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin and Follistatin—New Kids on the Block in the Diagnosis of Sarcopenia in IBD and Possible Therapeutic Implications

Abstract: Sarcopenia, which is a decrease in muscle strength and quality of muscle tissue, is a common disorder among patients suffering from inflammatory bowel disease. This particular group of patients often presents with malnutrition and shows low physical activity, which increases the risk of sarcopenia. Another important factor in the development of sarcopenia is an imbalanced ratio of myostatin and follistatin, which may stem from inflammation as well as genetic factors. Currently, research in this area continues,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 75 publications
0
13
0
1
Order By: Relevance
“…The myostatin-follistatin system has long been considered a possible target for sarcopenia therapies, and several clinical trials are ongoing, as reviewed by Skrzypczak and colleagues [ 37 ]. Although it is unclear whether these proteins are good biochemical markers to monitor the disease or the drug efficacy, myostatin and follistatin should be considered as a couple that helps decipher the physio-pathological drug mode of action.…”
Section: Methodsmentioning
confidence: 99%
“…The myostatin-follistatin system has long been considered a possible target for sarcopenia therapies, and several clinical trials are ongoing, as reviewed by Skrzypczak and colleagues [ 37 ]. Although it is unclear whether these proteins are good biochemical markers to monitor the disease or the drug efficacy, myostatin and follistatin should be considered as a couple that helps decipher the physio-pathological drug mode of action.…”
Section: Methodsmentioning
confidence: 99%
“…The loss of muscle is therefore thought to be secondary to an interaction between the environment and these underlying genetic predispositions. Whole genome studies, quantitative genetic mapping, DNA microarrays and microRNA studies in patients with sarcopenia have been published; unfortunately, the significant heterogeneity in the study design and genetic evaluations has led to substantial variability in the results 3 . While genes such as VDR, ACE and ACTN3 have been identified frequently in patients with sarcopenia, the clinical significance of this and the relationship of these genes in patients with IBD remain unclear and a focus for future research 3 …”
Section: Pathogenesis Of Sarcopenia In Ibdmentioning
confidence: 99%
“…Myostatin, a growth differentiation factor, is known to be a negative regulator of muscle biosynthesis and homeostasis 3 . Although this protein is found mostly in skeletal muscle, it has been shown that serum levels of myostatin increase with age and are inversely proportional to lean muscle mass 3 . Of interest, this protein is found to be particularly elevated in patients with sarcopenic obesity and insulin resistance 74 .…”
Section: Sarcopenia Clinical Assessment and Diagnosismentioning
confidence: 99%
See 2 more Smart Citations